Studying the high frequency seismic signals for enhanced knowledge of the shallow Earth structure and soil investigation - GAMAL, Mohamed A.; MAHER, George (Contributions to Geophysics and Geodesy, 2025)
The Earth acts like a low-pass filter to earthquake energy so that frequencies higher than 10 Hz are rapidly attenuated. This intrigues seismologists about the seismic waves in the frequency domain 1–10 Hz, which is crucial to correctly assess the impact of seismic shaking on structures. However, not much attention has been paid to higher frequencies, probably due to its low significance and structural damage. The Earth has high frequency seismic signal (HFSS) in the audible frequency range 20–20,000 Hz and maybe higher (Gamal et al., 2020). These seismic signals result from the transformation of any energy into HFSS energy which is propagated inside the Earth, this energy may be winds, the crustal structure movement, movement due to gravitational force or any mechanical energy transformed into high frequency seismic vibrations. Fifteen different geological environments were tested in Egypt, to monitor the high frequency seismic signals (HFSS) of the subsurface soil. The present study used very high digitising frequency seismographs, not less than 8,000 to 16,000 sample per second, and a set of horizontal and vertical geophones of natural frequencies in the ranges of 4 Hz to 100 Hz. It was found that consolidated rocks have high-pitch that may reach 4,000 Hz, while weak fractured soils sound have a low-pitch, in the frequency range of 20–70 Hz. Speech and audio processing methods have been used to differentiate between these HFSS preserved inside soils and to produce the “unified HFSS map”. The “Soil HFSS map” was considered as avail science could be used in the future to give deep insight on the shallow Earth’s interiors.